2023
DOI: 10.1371/journal.pgph.0000832
|View full text |Cite
|
Sign up to set email alerts
|

Factors that determine women’s autonomy to make decisions about sexual and reproductive health and rights in Nepal: A cross-sectional study

Abstract: Women’s autonomy on sexual and reproductive health issues is critical to women’s health and well-being. Women have the right to decide on their fertility and sexuality, be free from coercion and violence, and achieve well-being. This study has identified women’s autonomy regarding decision and exercise of their sexual reproductive health and rights and its association with determining factors in Nepal. Descriptive and analytical statistics such as bivariate and multivariate regression analysis were performed u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 30 publications
2
4
0
Order By: Relevance
“…Present findings are consistent with our previous research based on the 2013 NDHS [13] and a recent study investigating the association of age differences on the ‘non-use of ANC’ services in Nigeria [14]. Our results also agree with a recent Nepalese study [36], which found that women aged 15-19 years were less likely to be autonomous or able to exercise their sexual and reproductive rights.…”
Section: Discussionsupporting
confidence: 93%
“…Present findings are consistent with our previous research based on the 2013 NDHS [13] and a recent study investigating the association of age differences on the ‘non-use of ANC’ services in Nigeria [14]. Our results also agree with a recent Nepalese study [36], which found that women aged 15-19 years were less likely to be autonomous or able to exercise their sexual and reproductive rights.…”
Section: Discussionsupporting
confidence: 93%
“…This could be because the wealth quintile did not include household income and overseas remittances or because the women got special support. In addition, increased age was one of the determinants of decision-making toward sexual and reproductive health in Nepal [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…For example, Sadhu et al (2020) and Acharya et al (2010) found that in rural Rajasthan and Nepal, as a woman ages, she tends to gain greater autonomy regarding unrestrained movement than a younger woman. Thus, as women age, they gain greater autonomy in household decision-making in polygamous relationships and may acquire additional responsibilities to mentor and guide the decisions of younger women/co-wives (Hanmer and Klugman, 2016;Nepal et al, 2023). In a Southern Ethiopian study about women's autonomy and contraceptive use, the authors found that although women aged 21-30 years were twice as likely to participate in household decisionmaking autonomy, those who were 30 years and older were seven times more likely to participate in decision-making autonomy (Alemayehu and Meskele, 2017) alluding to the importance of age in the power dynamics within a polygamous household.…”
Section: Respondent Alone 13mentioning
confidence: 99%